Isolation and characterization of a c-repeat binding factor gene from Tevang-1 maize cultivar - Linh, Nguyen Thuy; Ly, Luu Han; Duong, Nguyen Thuy; Hue, Huynh Thi Thu (Academia Journal of Biology, 2019)
C-repeat binding factor (CBF) proteins are transcription factors involved in plant response to abiotic stresses, especially low-temperature condition. In this research, a CBF3-coding gene was isolated from a cold-acclimation maize variety, Zea mays var. Tevang-1 and denoted as ZmCBF3tv. The isolated gene shared 96.49% homology with the B73-reference gene and had no intron in the coding sequence. By using bioinformatic tools, a number of variations in the nucleotide and amino acid sequences were identified. An alignment between ZmCBF3tv and other CBF/DREB1 proteins from various species revealed functional regions and typical features, such as nuclear localization signal (NLS), the AP2 DNA-binding domain, and acidic-amino-acid-rich segments. Additionally, a phylogenetic analysis based on the AP2 domain showed that the maize CBF3 transcription factor had the highest similarity with that from rice and closely related to other DREB1/CBF protein of monocots. The function of the ZmCBF3tv product is suggested to be a CBF/DREB1 transcription factor.